Towards Accuracy: A Model for the Analysis of Typographical Errors in Specialised Bilingual Dictionaries. Two Case Studies - Rodríguez-Rubio, Santiago; Fernández-Quesada, Nuria (Lexikos, 2020)
This paper presents the results of research on typographical error analysis in two specialised bilingual paper dictionaries: Diccionario de términos económicos, financieros y comerciales/ A Dictionary of Economic, Financial and Commercial Terms (Ariel, 2012), and Diccionario de términos jurÃdicos/A Dictionary of Legal Terms (Ariel, 2012). A model of errors is described, including similar errors and errors that are repeated both intratextually and intertextually. The error frequency in A Dictionary of Economic, Financial and Commercial Terms is higher than the average error frequency in a reference corpus of fourteen dictionaries (mainly first editions). This indicates that repeated editions do not always guarantee a higher level of formal correctness. Our results also show that a high frequency of errors does not necessarily entail a high intratextual error repetition rate. On the other hand, we establish a relationship between typographical errors and the access function in dictionaries, as that kind of error can interfere with access to accurate lexicographical information and data retrieval (especially when they occur in lemmas or sublemmas).